Achieving SDG 2 in east java: Agriculture and food security office’s role - Hariyanti, Carelia Pradita (Faculty of social and Political sciences, Hasanuddin University, 2025)
The global food security crisis, exacerbated by climate change, conflicts, and pandemics, has led to millions suffering from hunger and malnutrition. In Indonesia, the prevalence of stunting remains high, necessitating urgent action to achieve Sustainable Development Goal (SDG) 2, which aims for